BIOLOGY OF PAPAYA MEALY BUG Paracoccus marginatus (HEMIPTERA: PSEUDOCOCCIDAE) IN CASSAVA (Manihot utilissima Pohl) - Husni Husni; Nur Pramayudi; Mutia Faridah (Universitas Syiah Kuala, 2012)
The biology of papaya mealy bug (Paracoccus marginatus) in the cassava (Manihot utilissima) had been studied at the Plant Protection Laboratory of the Agriculture Faculty of Syiah Kuala University. The purpose of this study was to investigate the biology of P. marginatus on the cassava leaves. The result showed that the insect development time on cassava leaves were: 8.0 ± 0.79 days for egg stage, 5.3 ± 0.67 days for first instar nymph, 5.5 ± 0.84 days for the second instar of female nymph, 5.3 ± 0.50 days for the second instar of male nymph, 5.4 ± 0.51 days for the third instar of female nymph, and 3.6 ± 0.52 days for the third instar of male nymph (pre pupa), respectively. The development time of IV instar of male nymp (pupa) was 56,6 ± 0,58 days. The development time of the adult stage for female and male progeny were 14 ± 1,24 days and 43,3 ± 0,58 days. The life cycle of female and male were 31,8 ± 3,83 days and 27,8 ± 1,87 days, and the average number of eggs in each ovisac was 413, respectively.